Nonalcoholic Fatty Liver Disease Incidence and Remission and Their Predictors During 7 Years of Follow-up Among Finns - Korpimäki, S. (ENDOCRINE SOC, 2025)
Background & aims: The incidence and remission of non-alcoholic fatty liver disease (NAFLD) are sparsely studied outside Asia. This prospective study aimed to investigate NAFLD incidence and remission, and their predictors among a general Finnish population.
Methods: The applied cohort included 1260 repeatedly studied middle-aged participants with data on liver ultrasound and no excessive alcohol intake. Hepatic steatosis was assessed by liver ultrasound with 7.2-year study interval. Comprehensive data on health parameters and lifestyle factors were available.
Results: At baseline 1079 participants did not have NAFLD, and during the study period 198 of them developed NAFLD. Of the 181 participants with NAFLD at baseline, 40 achieved NAFLD remission. Taking multicollinearity into account, key predictors for incident NAFLD were baseline age (odds ratio 1.07, 95% confidence interval 1.02-1.13, P=0.009), waist circumference (WC) (2.77, 1.91-4.01 per one standard deviation [SD], P<0.001), and triglycerides (2.31, 1.53-3.51 per one SD, P<0.001) and alanine aminotransferase (ALAT) (1.90, 1.20-3.00 per one SD, P=0.006) concentrations as well as body mass index (BMI) change (4.12, 3.02-5.63 per one SD, P<0.001). Predictors of NAFLD remission were baseline aspartate aminotransferase (ASAT) concentration (0.23, 0.08-0.67 per one SD, P=0.007) and WC change (0.38, 0.25-0.59 per one SD, P<0.001).
Conclusions: During the follow-up, NAFLD developed for every fifth participant without NAFLD at baseline, and a fifth of those with NAFLD at baseline had achieved NAFLD remission. NAFLD became more prevalent during the follow-up. From a clinical perspective, key factors predicting NAFLD incidence and remission were BMI and WC change independent of their baseline level.